CXCL11 mediates TWIST1-induced angiogenesis in epithelial ovarian cancer - Yu-Jin Koo; Tae-Jin Kim; Kyung-Jin Min; Kyeong-A So; Un-Suk Jung; Jin-Hwa Hong (Tumor Biology)
To investigate the role of TWIST1 in tumor angiogenesis in epithelial ovarian cancer and to identify key molecules involved in angiogenesis. TWIST1 small interfering RNA was transfected into A2780 cells, while a complementary DNA vector was transfected into non-malignant human ovarian surface epithelial cells to generate a TWIST1-overexpressing cell line. To evaluate how this affects angiogenesis, human umbilical vein endothelial cell tube formation assays were performed using the control and transfected cell lines. An antibody-based cytokine array was used to identify the molecules involved in TWIST1-mediated angiogenesis. After knockdown of TWIST1 via transfection of TWIST1 small interfering RNA into A2780 cells, the number of tubes formed by human umbilical vein endothelial cells significantly decreased in a tube formation assay. In a cytokine array, TWIST1 downregulation did not significantly decrease the secretion of the common pro-angiogenic factor, vascular endothelial growth factor, but instead inhibited the expression of the CXC chemokine ligand 11, which was confirmed by both an enzyme-linked immunosorbent assay and western blotting. In contrast, TWIST1 overexpression resulted in increased secretion of CXC chemokine ligand 11. Conversely, CXC chemokine ligand 11 downregulation did not inhibit the expression of TWIST1. Furthermore, the ability of TWIST1-expressing A2780 cells to induce angiogenesis was found to be inhibited after CXC chemokine ligand 11 knockdown in a tube formation assay. TWIST1 plays an important role in angiogenesis in epithelial ovarian cancer and is mediated by a novel pro-angiogenic factor, CXC chemokine ligand 11. Downregulation of CXC chemokine ligand 11 can inhibit tumor angiogenesis, suggesting that anti–CXC chemokine ligand 11 therapy may offer an alternative treatment strategy for TWIST1-positive ovarian cancer.